2014
DOI: 10.1039/c4ra05869k
|View full text |Cite|
|
Sign up to set email alerts
|

Complexing agent study via computational chemistry for environmentally friendly silver electrodeposition and the application of a silver deposit

Abstract: Predicting the complexing agents used for a new environmentally friendly silver electroplating bath by computational chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 68 publications
0
33
0
Order By: Relevance
“…The curves all sweep from the rest potential to the negative direction. The literature [18] has revealed that DMH is easy to absorb on electrode surface. The cathodic peak c1 appears in all three curves although it is very small in Ni voltammogram.…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
See 1 more Smart Citation
“…The curves all sweep from the rest potential to the negative direction. The literature [18] has revealed that DMH is easy to absorb on electrode surface. The cathodic peak c1 appears in all three curves although it is very small in Ni voltammogram.…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…Their results showed that all of those amines were good complexing agents and a homogeneous composition of Zn-Ni alloy can be obtained. Up to now, 5,5′-dimethylhydantoin(DMH) is often used as a complexing ligand in Au [17] or Ag [18] deposition. To the best of our knowledge, there is no report on the application of DMH used as a complexing ligand in Zn-Ni alloy deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks c1 and a3 also appear in Zn only and Ni only bath. The literature 15 has revealed that DMH is easy to adsorb on electrode surface. This indicates that c1 and a3 are related to the adsorption and desorption of DMH on Pt electrode, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group has successfully used 5,5 -dimethylhydantoin (DMH) as the main complexing agent to electrodeposit Au, 14 Ag, 15 and Cu 16 in alkaline non-cyanide bath. According to their results, it can be concluded that DMH mainly has two different roles in metal electrodeposition.…”
mentioning
confidence: 99%
“…The bright Zn-Ni 3 relatively low current efficiency, leaving it impossible for commercial use. 49 5,5'-dimethylhydantoin (DMH) has been successfully used in Au, 17 Ag 18 and Cu 19 50 electrodeposition and it is a promising complexing agent in Zn-Ni alloy deposition 51 owing to the large stability constants of DMH with Zn 2+ and Ni 2+ . 20 According to our 52 previous studies, 6,21 the investigated new alkaline Zn-Ni alloy bath has a high 53 stability and the aged baths have little effect on the electrochemical behaviors of the 54 investigated electrolyte.…”
Section: Introductionmentioning
confidence: 99%